Seroprevalence of Foot and Mouth Disease Virus Infection in Some Wildlife and Cattle in Bauchi State, Nigeria - Y. J. Atuman; C. A. Kudi; P. A. Abdu; O. O. Okubanjo; A. Abubakar; Y. Wungak; H. G. Ularamu (Veterinary Medicine International)
Foot and mouth disease (FMD) is an important transboundary viral disease of both domestic and wild cloven-hoofed animals characterized by high morbidity with devastating consequence on the livestock worldwide. Despite the endemic nature of FMD in Nigeria, little is known about the epidemiology of the disease at the wildlife-livestock interface level. To address this gap, blood samples were collected between 2013 and 2015 from some wildlife and cattle, respectively, within and around the Yankari Game Reserve and Sumu Wildlife Park in Bauchi State, Nigeria. Wild animals were immobilized using a combination of etorphine hydrochloride (M99® Krüger-Med South Africa) at 0.5–2 mg/kg and azaperone (Stresnil®, Janssen Pharmaceuticals (Pty.) Ltd., South Africa) at 0.1 mg/kg using a Dan-Inject® rifle (Dan-Inject APS, Sellerup Skovvej, Denmark) fitted with a 3 ml dart syringe and for reversal, naltrexone (Trexonil® Kruger-Med South Africa) at 1.5 mg IM was used, and cattle were restrained by the owners for blood collection. Harvested sera from blood were screened for presence of antibodies against the foot and mouth disease virus (FMDV) using the PrioCHECK® 3ABC NSP ELISA kit, and positive samples were serotyped using solid-phase competitive ELISA, (IZSLER Brescia, Italy). Out of the 353 sera collected from cattle and wildlife 197 (65.7%) and 13 (24.5%) (P<0.05), respectively, tested positive for antibodies to the highly conserved nonstructural 3ABC protein of FMDV by the FMDV-NS blocking ELISA. Classification of cattle into breed and sex showed that detectable antibodies to FMDV were higher (P<0.05) in White Fulani 157 (72.8%) than in Red Bororo 23 (39.7%) and Sokoto Gudali 17 (33.3%) breeds of cattle, whereas in females, detectable FMDV antibodies were higher (P<0.05) 150 (72.8%) than in males 47 (50.0%). In the wildlife species, antibodies to FMDV were detected in the waterbucks 2 (28.6%), elephant 1 (25.0%), wildebeests 4 (33.3%), and elands 6 (25.0%). Four serotypes of FMDV: O, A, SAT 1, and SAT 2 were detected from the 3ABC positive reactors in waterbucks, elephants, wildebeests, and elands. The results showed presence of antibodies to FMDV in some wildlife and cattle and suggested that wildlife could equally play an important role in the overall epidemiology of FMD in Nigeria. FMD surveillance system, control, and prevention program should be intensified in the study area.